IMPLEMENTASI PROGRAM KAS-RPA KAMPUNG ASUH DALAM MEWUJUDKAN SURABAYA KOTA LAYAK ANAK - Lutfiatul Laili Arrohmati; Vidya Imanuari Pertiwi (Journal Publicuho, 2024)
KAS-RPA is a Surabaya City government program in the context of realizing Surabaya as a child-friendly city. This program consists of five indicators, namely, learning villages, healthy villages, assisted villages, safe villages and productive creative villages. This research aims to examine various aspects, human resources, communication between organizations, the disposition of implementers, and bureaucratic structures that contribute to the successful implementation of (the KAS-RPA) foster village. The method used is descriptive qualitative, with primary and secondary data sources used through direct interviews and participant observation. The research focus of this study is to describe the factors for the success of implementing the foster village program in order to create Surabaya, a child-friendly city in RT 4, RW 2, Sidosermo Village, Surabaya. The results of this research indicate that the implementation of the KAS-RPA foster village program was successful due to the following factors, including good inter-organizational communication, good characteristics of implementing agents, and responsiveness of competent human resources.